Simulation and Optimization of Ammonia Converter on Increasing the Mole Percent of Ammonia Products in the Ammonia Plant Through Modification Process - Raissa Nur Hafidza; Emily Taqiy Ramadhani Soesilo; Asvia Icha Bilbina; Abdulhaq Mahatir Ramadani; Raihan Yafi Aqila (UPT Laboratorium Terpadu, Universitas Diponegoro, 2025)
Ammonia production efficiency is strongly influenced by temperature management within the multi-bed converter, where deviations from optimal conditions often reduce the final ammonia mole fraction compared to design expectations. To address this challenge, the ammonia synthesis loop was modified by adding a cooler and a heat exchanger between Bed-2A and Bed-2B to achieve more controlled inter-stage temperatures and improve equilibrium conversion. A complete process model was constructed in process simulation software using actual operating data, allowing evaluation of the original thermal profile and ammonia formation across each catalytic bed, followed by simulation of the modified configuration to quantify performance improvements. The optimized arrangement successfully increased the final ammonia mole fraction from 15.97% to 17.74%, approaching the design target of 19.02%, while maintaining temperatures closer to the ideal range for exothermic synthesis reactions. These results highlight that carefully targeted thermal adjustments and strategic heat integration can enhance reaction efficiency, reduce temperature-induced conversion losses, and provide a practical, implementable pathway for improving ammonia yield in existing industrial plants. Copyright © 2025 by Authors, Published by Universitas Diponegoro and BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).